Evidence of increased exposure to Toxoplasma gondii in individuals with recent onset psychosis but not with established schizophrenia. - Robert Yolken; E Fuller Torrey; Faith Dickerson (Public Library of Science (PLoS), 2017)
A possible role for Toxoplasma gondii in the etiopathogenesis of schizophrenia is supported by epidemiological studies and animal models of infection. However, recent studies attempting to link Toxoplasma to schizophrenia have yielded mixed results. We performed a nested case-control study measured serological evidence of exposure to Toxoplasma gondii in a cohort of 2052 individuals. Within this cohort, a total of 1481 individuals had a psychiatric disorder and 571 of were controls without a psychiatric disorder. We found an increased odds of Toxoplasma exposure in individuals with a recent onset of psychosis (OR 2.44, 95% Confidence Interval 1.4-4.4, p < .003). On the other hand, an increased odds of Toxoplasma exposure was not found in individuals with schizophrenia or other psychiatric disorder who did not have a recent onset of psychosis. By identifying the timing of evaluation as a variable, these findings resolve discrepancies in previous studies and suggest a temporal relationship between Toxoplasma exposure and disease onset.